LITERATURE REVIEW : INTERVENTIONS IMPROVING QUALITY OF LIFE IN PATIENTS WITH BREAST CANCER - Lilis Mamuroh; Printin Sari; Dian Trias Oktavianti; Muhammad Faidzal Muttaqin; Nursita Dewi; Razzy Purnama; Aneu Agustiani; Siti Nur Asiah (Journal of Maternity Care and Reproductive Health, 2021)
Clinically the quality of life of breast cancer sufferers has decreased since being diagnosed with being diagnosed with breast cancer and can continue periodically every year. Breast cancer is a malignancyoriganiting from the glands, glandular ducts and supportingtissues excluding the skin of the breast. Breast  cancer cells cuolds spread through the bloodstream throughout the body. Palliative therapy is usually given to breast cancer patients to maintain their physical, psychological, social, spiritual qualities with the aim of relieving the symptoms that appear so that the patient’s quality of life will improve as optimally as possible. The purpose of this literature review is to determine which interventions are effective in improving the quality of life of patients with breast cancer. This research methode is a literature study, by searching using Efidence Based Practice ( EBP ) from database such as Pubmed, Proquest and Google Scholar. There are seven articles based on the results of searching using the PICO technique. After conducting an article search, seven research articles that fit the inclusion criteria were selected. The interventions carried out to improve the quality of life of patients with breast cancer from each article are different, including (1) beauty care (2) spiritual support (3) virgin coconut oil therapy (4) live review therapy (5) Supportive Expression Group Therapy (6) yoga and (7) Progressive Muscle Relaxation.  There are similarities in the results of the seven journals that have been reviewed, namely that they can improve the quality of life for breast cancer sufferers. Therefore,it is hoped that the results  of this  literature  review can be used as a source of information and could be directly practiced as an intervention to improve the quality of life in patients with breast cancer.